Turkey’s Democratic Process and International Stability after Helsinki: A Research Agenda - Tsakonas, Panayotis J.; Constas, Dimitri C. (Études helléniques / Hellenic Studies, 2000)
An effort will be made in this article to set up a research agenda, with the aim of highlighting the key issues which, due to decisions made at the Helsinki Summit, are expected to dominate both the Greek-Turkish security agenda as well as the EU-Turkey political agenda in the coming months and even years. To this end, the article will discuss the effects of the democratization process on forcing policy decision-making of an anocratic (a mixture of democratic and autocratic characteristics) regime, namely Turkey. It is the thesis of this article that the developments and changes in Turkey’s domestic arena are those which will most seriously influence Turkey’s foreign policy decisions towards cooperation or conflict with neighboring Greece and are thus those which deserve analysis in the current turbulent ‘democratization process’ . Herein also lies the policy relevance of this project, namely to make all external actors either interested or involved in the EU-Turkish project aware of the risks involved in the turbulent transition period ushered in by the Helsinki Summit.